Sistem Pemeliharaan dan Perawatan Bahan Pustaka di Sekolah UPTD SDN 015864 Desa Rawang Lama Pasar IV - Dinda Aprilia Putri; Intan Fajira; Indah Rohyani; Ari Yanto (PT. ALHAFI BERKAH INDONESIA, 2025)
Damage to library materials occurs due to environmental factors such as light, temperature, humidity and air which also speed up the process. Other causes of damage include humans and animals, mold dust and chemical damage to library materials. Other causes of damage are bookshelves that are not suitable for use for library materials and lack of awareness among users of library materials. Based on observations made by the author in the UPTD SDN 015864 Desa Rawang Lama Pasar IV School library, maintenance of library materials still needs to be improved. Therefore, there is a lot of damage to library materials that occurs in libraries, moreover, librarians are not very careful in maintaining and caring for library materials. With the group visit, we hope to be able to help librarians in caring for and maintaining library materials